Geochemical and sedimentological analyses on the Romanian Sphagnum peat bog Tăul fără fund - Tamás Zsolt Vári; Pál Sümegi (Mires and Peat, 2024)
This study focuses on palaeoenvironmental changes in the Bottomless Lake (Tăul fără fund) Sphagnum peat bog situated near Bǎgǎu in Romania. The central research question was how the lake has changed over time, and how environmental factors and human activities have influenced the changes. By employing previous loss-on-ignition and radiocarbon analyses in addition to new radiocarbon, grain size, magnetic susceptibility and geochemical analyses, a more precise reconstruction of the bog's regeneration and erosion phases was achieved. A multi-proxy analysis of the core sequence provided crucial insights regarding the interconnections between various elements. Notably, plant-derived elements (Na, K) exhibited correlations with organic matter, and carbonate elements (Ca, Mg) with carbonate content; while Fe and magnetic susceptibility displayed changes in relation to inorganic matter content. Remarkably, the findings reflected the global 8200 cal BP and 4200 cal BP events, along with their environmental effects, within the Transylvanian Basin. There was mediaeval lakebed cleaning around 500300 cal BP, during which the deeper of two water layers was contaminated with more recent materials. The shallower water layer is connected with the modern water circulation, which reduces the apparent age of peat samples taken from its immediate vicinity.